A case of long-term survival after repeated response to oxaliplatin-based chemotherapy and repeated thermoablation of liver metastases from colorectal cancer. Should we introduce the concept of oxaliplatin-resistant tumors?. Issue 3 (May 2013) - Ottone, Azzurra; Bellini, Elisa; Ferrero, Anna; Baratelli, Chiara; Taberna, Eleonora; Bitossi, Raffaella; Brizzi, Maria Pia; Tampellini, Marco
Background: The management of advanced colorectal cancer patients differs among cancer centers. International guidelines recommend offering all the recognized active regimens in order to obtain survival advantage, but little information is given about the sequence and combination in which such regimens should be administered. Case report: We report the case of a man with multiple liver metastasis from colorectal cancer followed for more than 78 months at our Institution. Repeated response to the same oxaliplatin, 5-fluorouracil and folinic acid chemotherapy schedule was achieved, and repeated radiofrequency ablation of liver metastases was performed until progression of lung and brain disease at 50 and 72 months, respectively, after the diagnosis of advanced disease. Although the tumor became oxaliplatin and chemo-resistant after the onset of extra-hepatic disease, a more aggressive chemotherapy regimen, including a doublet with a biological, halted tumor growth. Conclusions: The patient survived for more than 78 months without experiencing a major impact on his quality of life. This case reflects the importance of following tumor biology in the therapeutic decision-making process, reintroducing oxaliplatin whenever possible, and adopting a more aggressive strategy when the tumor becomes oxaliplatin-resistant.